Evaluation of the feasibility, acceptability, and impact of Group Antenatal Care at the health post level on continuation in antenatal care and facility based delivery in Ethiopia using a cluster randomized stepped-wedge design: Study protocol [version 3; peer review: 1 approved, 3 approved with reservations, 1 not approved] - Reena Sethi; Rediet Fasil; Walelegn W. Yallew; Della Berhanu; Yenealem Woldemariam; Gayane Yenokyan; Alemayehu Worku; Dedefo Teshite; Konjit Wolde; Anne Hyre; Stephanie Suhowatsky; Lisa Noguchi (Gates Open Research)
Background Adequate antenatal care (ANC) and facility-based delivery are linked to improved maternal and neonatal outcomes. Adequate ANC attendance and facility birth rates are increasing in Ethiopia but remain well below national goals and global recommendations. Group ANC (G-ANC), when implemented at higher-level facilities, is associated with improved quality and experience of ANC and increased ANC retention and facility-based delivery. The objectives of this study are to evaluate the acceptability, feasibility, and effectiveness of G-ANC delivered by health extension workers at the health-post level compared to conventional ANC on ANC attendance and facility-based delivery. Methods Group ANC will be piloted in five purposively selected health posts. The study design is a stepped-wedge trial to be conducted in 36 health posts within the catchment of six health centers, with randomization of the order of the intervention introduction done at the health-center level (clusters). The design includes three time periods: a six-month control period with no G-ANC implementation, followed by another six-month period when G-ANC will be introduced in half (n=18) of the study health posts, then a final six-month period when G-ANC will be implemented in the remaining 18 health posts. Each health post will form one cohort and conduct six monthly G-ANC meetings on a fixed day/time. The study will use quantitative and qualitative data collection approaches. The study has “pause and reflect” points designed for intervention iteration before rolling out to the next set of sites. The primary outcomes are the proportion of women with at least four ANC visits and the proportion who delivered in a health facility. Qualitative research will be conducted using in-depth interviews with pregnant women, health workers, facility managers, and regional health managers. The study will enroll 770 women across all phases. Conclusions The study will inform decision-makers locally and globally on whether G-ANC is a feasible service delivery model at the health-post level. Effectiveness of G-ANC at increasing ANC retention and facility-based delivery and its acceptability to pregnant women and health extension workers will be reported. Registration NCT05054491, ClinicalTrials.gov (September 23, 2021).